2009
DOI: 10.1111/j.1364-3703.2009.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in the tomato root transcriptome on infection with the potato cyst nematode Globodera rostochiensis

Abstract: Plant parasitic nematodes infect roots and trigger the formation of specialized feeding sites by substantial reprogramming of the developmental process of root cells. In this article, we describe the dynamic changes in the tomato root transcriptome during early interactions with the potato cyst nematode Globodera rostochiensis. Using amplified fragment length polymorphism-based mRNA fingerprinting (cDNA-AFLP), we monitored 17 600 transcript-derived fragments (TDFs) in infected and uninfected tomato roots, 1-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 72 publications
(126 reference statements)
1
30
0
Order By: Relevance
“…Using the cDNA-AFLP method, Swiecicka et al (2009) found that five genes analysed in the present study were up-regulated in G. rostochiensis -infected roots from 1 to 14 dpi, but the highest transcript accumulation was observed at 1 and/or 3 dpi. To verify this finding and to confirm our results obtained using promoter- gusA fusions, the expression of the CYP97A29 , DFR , FLS , NIK and PMEI genes in infected and uninfected tomato plants was studied by semi-quantitative RT-PCR.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Using the cDNA-AFLP method, Swiecicka et al (2009) found that five genes analysed in the present study were up-regulated in G. rostochiensis -infected roots from 1 to 14 dpi, but the highest transcript accumulation was observed at 1 and/or 3 dpi. To verify this finding and to confirm our results obtained using promoter- gusA fusions, the expression of the CYP97A29 , DFR , FLS , NIK and PMEI genes in infected and uninfected tomato plants was studied by semi-quantitative RT-PCR.…”
Section: Resultssupporting
confidence: 50%
“…Genes were selected from a set of tomato genes that were shown to be up-regulated after G. rostochiensis infection by Swiecicka et al (2009) (Table S1). The 5′ upstream regions of these genes were amplified using a BD Advantage™ Genomic PCR kit (BD Biosciences Clontech) from adaptor-ligated tomato genomic libraries prepared by the GenomeWalker™ protocol (BD Bioscences Clontech).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, various members of MYB (GW276033), AP2/EREBP (GW276030) and WRKY (GW275998 and GW276009) TF families, as identified in this study, have been shown to be implicated in controlling gene expression in various abiotic and biotic stress signal transduction pathways. Swiecicka et al (2009) also observed a significant differential in the induction of TF gene family members in tomato roots during early and late stages of potato cyst nematode G. rostochiensis infection, and suggested a direct functional involvement for TFs in stress responses as well as feeding site development. Nematode-induced MYB122 in Florunner roots is a member of the clade I subgroup of 12 R2R3-MYB TFs and a regulator of indolic glucosinolate biosynthesis, central to defense against herbivores and pathogen attack (Gigolashvili et al, 2009).…”
Section: Nematode-induced Changes In Transcriptional/translational Rementioning
confidence: 81%
“…Transcriptome and microarray analyses of host roots infected with plant nematodes showed differential changes in the expression of genes responding to several hormones including auxin, ethylene (ET), jasmonic acid (JA), salicylic acid (SA), brassinosteroids (BR), gibberellins (GA), and abscisic acid (ABA)222324. A number of studies have indicated that the signaling pathways of SA, JA, BR, ABA, and ET are involved in the defense response of host plants to nematodes252627282930.…”
mentioning
confidence: 99%